The Influence of Good Corporate Governance, Tax Planning, and Financial Distress on Earnings Management with Internal Control as Intervening Variable - Alfiana Alfiana; Fitriana Rakhma Dhanias; Loso Judijanto; Hadi Purnomo; Dipa Teruna Awaludin (Lembaga Riset dan Inovasi Al-Matani, 2026)
This study examines the influence of good corporate governance, tax planning, and financial pressure on earnings management in State-Owned Enterprises (SOEs) in Indonesia, with internal control as an intervening variable. This study is motivated by the limited research integrating the role of internal Control in the relationship between governance mechanisms and earnings management, particularly in the context of SOEs. The study sample consisted of 20 SOEs listed on the Indonesia Stock Exchange during the 2018–2023 period, yielding 120 company-year observations selected via purposive sampling. Data analysis was performed using a random-effects model (REM) in EViews 12. The results show that corporate governance and financial pressure do not significantly influence earnings management, although both are negative. Tax planning has a significant negative effect on earnings management. Internal control is proven to have a significant negative effect, but is unable to mediate the relationship between the independent variables and earnings management. These findings emphasize the importance of strengthening internal control to suppress earnings management practices and provide an empirical contribution regarding the limited role of governance mechanisms in the context of SOEs.